IDENTIFICATION OF A GROSS DELETION MUTATION OF GLA GENE IN A FABRY DISEASE FAMILY CHARACTERIZED BY ATRIAL FIBRILLATION AND MYOCARDIAL HYPERTROPHY. (June 2022) - Lu, Yiting; Fan, Peng; Zhou, Xianliang
Abstract : Objective: Fabry disease is a rare X-linked lysosomal storage disease caused by GLA gene mutations, which results in the deficient activity of -galactosidase A. The decreased enzymatic activity consequently leads to abnormal accumulation of the substrate glycosphingolipids in multi-organ. Herein, we reported a Chinese family with Fabry disease predominantly characterized by atrial fibrillation and myocardial hypertrophy. Design and method: We collected venous blood samples from all participants and genomic DNA was exacted for genetic testing. Conventional GLA cDNA analysis and multiplex ligation-dependent probe amplification (MLPA) analysis was performed in a Chinese family highly suspected of Fabry disease. Results: Genetic analysis identified a gross deletion (IVS1_IVS2del) in GLA gene in the proband and other 3 family members. There was a large deletion on both sides of the 5' breakpoint of the first Alu repeat in intron 1 and the 3' breakpoint of the seventh Alu repeat in intron 2, which may be caused by the recombination of AluAlu repeat. The proband mainly presented with cardiac symptoms, including atrial fibrillation and myocardial hypertrophy. Family history of heart disease was positive, including index' maternal uncle and grandmother who died of sudden cardiac death, index' mother and aunt with atrial fibrillation and myocardial hypertrophy. All affected patients had insufficient -galactosidase A activity. Conclusions: The phenotype of Fabry disease is complex and variable. Patients with Fabry disease are often complicated with cardiac involvement, which may be neglected easily. Enzyme activity test and genetic analysis are effective methods for the precise diagnosis of Fabry's disease.